The complete guide to managing a portfolio of mutual funds - Rutherford, Ronald K. (New York : McGraw-Hill, 1998)
The Complete Guide to Managing a Portfolio of Mutual Funds makes the case that, when chosen with skill and knowledge, mutual funds continue to be an excellent base upon which to build portfolios.
Author Ron Rutherford illustrates investment strategies he used to become one of the country's foremost financial planners. His book, complete with more than 100 charts, graphs, and figures, provides ideas that advisors can use to help their clients, as it details: The Investment Policy Statement - Use Rutherford's proven approach to construct an IPS that is not only a decision-making aid but a tool for communicating with your client; Asset Class Investing - The book discusses not only traditional mean variance optimization, but also other techniques such as benchmark optimization and downside risk with minimum acceptable return. These are approaches about the management of risk designed to raise the comfort level of the client; and Passive vs.
Active Investing - As the debate rages, Rutherford explains how the two terms are often misunderstood, may even be obsolete, and how you should view mutual fund investing in this context.
Rutherford supplies hard information, research, and immediately serviceable tips, including a review of some of today's best mutual fund managers, based on the consistency of their long-term records; critical statistics to look for in finding quality managers and their funds; how to use the portfolio method and the returns method as complementary tools to identify and monitor manager style; when and how to fire a manager; the appropriate positioning of index funds and the relatively new "enhanced index funds" in a client portfolio; and demonstration of some of the best software titles to design portfolios and to select mutual fund managers.
Includes bibliographical references and index.
Keywords: Mutual funds; Portfolio management; Gestion de portefeuille; Mutual funds; Portfolio management; Index funds